Fortalecimiento de la industria textil y de confección frente al contrabando (2022)
The textile and clothing industry has been and is one of the most representative sectors in the country, especially in international trade operations, however, as import volumes have increased, smuggling has also increased, therefore, the main objective of this work is to characterize the tax evasion of import processes in the textile and clothing sector in Colombia and to carry out this characterization the following objectives have been carried out, the description of the behavior of the textile sector and of clothing in the last 5 years, it was identified which are the controls established to reduce tax evasion and through a DOFA it was sought to establish which is the strengthening of control policies to reduce tax evasion. The main conclusion is based on the controls that have been established by control and customs agencies and on the opportunities that the sector can take advantage of for its growth in new technologies. The methodology carried out is based on investigations of figures, dates, data and interviews.